Akulturasi Desain Arsitektur Candi Pada Rancangan Pelinggih di Pura Giri Nata, Kediri, Jawa Timur - Aritama, Anak Agung Ngurah; Bharuna S, Anak Agung Gde Djaja; Mudra, I Ketut; Oka, I Gusti Bagoes (Jurnal Arsitektur Universitas Udayana, 2025)
An architectural object's design is an expression of the designer's application of science, technology, and art. Candi architecture is one style of building that has been preserved from the Indonesia's ancestors. A typical design, the candi is a place of worship for individuals who are enshrined in the temple. As time went on, research into and the discovery of different candi artifacts served as inspiration for a variety of new styles. As a result, the candi has gone through numerous forms of acculturation and a change in form, function, and appearance in the modern day. This essay will discuss how the architecture of Pura Giri Nata in Kediri, East Java, combined elements of Balinese and candi architecture. A qualitative approach to architecture's form, space, and accompanying style is the research methodology employed. Together with form and meaning descriptions, the data are presented as design drawings and three-dimensional representations. The study's findings are presented as a design acculturation model involving engineering insights into the shape and look of local architecture. Keywords: Acculturation, Candi Architecture, Balinese Architecture, Giri Nata Temple